The Palgrave Handbook of African Politics, Governance and Development (Palgrave Macmillan US, 2018)
This handbook constitutes a single collection of well researched articles and essays on African politics, governance and development from the pre-colonial through colonial to the post-colonial eras. Over the course of these interconnected periods, African politics have evolved with varied experiences across different parts of the continent. As politics is embedded both in the economy and the society, Africa has witnessed some changes in politics, economics, demography and its relations with the world in ways that requires in-depth analysis. This work provides an opportunity for old and new scholars to engage in the universe of the debate around African politics, governance and development and will serve as a ready reference material for students, researchers, policy makers and investors that are concerned with these issues.